BIOACTIVE COMPOUNDS AND FUNCTIONAL PROPERTIES OF SOME FLOUR COMPOSITES IN THE MANUFACTURING OF FUNCTIONAL FOOD PRODUCTS - Debby Moody SUMANTI; Imas Siti SETIASIH; Roostita L.BALIA; Agung KARUNIAWAN; Hendronoto Arnoldus W. LENGKEY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Composite flour from banana corm, sweet potato, and black soybean has rich nutrition content and contains bioactive compounds, which potentially benefficial for human health if consumed in proper amount. It is important to know composite flour properties prior apply to food product. The objective of this research was to determine the bioactive compounds and functional properties of composite flour that can be applied for functional food products. The method used was an experimental method by descriptive analysis with two replications. Composite flour made by mixture of 55 part banana corm flour, 45 part of sweet potato flour and black soybean flour added as much 20 percent of the weight of banana corm and sweet potato flours. The result showed that the composite flour had bioactive compounds which contained 9.09 g/ 100g of total phenols, 1.62 g/ 100g of tannins, 171.35 mg/ 100g of isoflavones, and IC50 979.64 ppm of antioxidant activity (very weak). The amylograph characteristic pasting involves initial temperature of gelatinization 76.620C, 1304.5 cP of peak viscosity, 930.0 cP of hot pasta viscosity, 1267.5 cP of cold pasta viscosity, 374.5 cP of breakdown viscosity and 337.50 cP of setback viscosity. Therefore, the composite flour from banana corm, sweet potato, and black soybean has rich nutritions to be used as functional food.